CD56(bright)CD25(+) NK cells are preferentially recruited to the maternal/fetal interface in early human pregnancy - Tao, Yu (Cell Mol Immunol, 2015)
Decidual natural killer (dNK) cells are believed to be critical for maintaining maternal/fetal tolerance and regulating placental vascular remodeling based upon their abundance and unique phenotype during early pregnancy. However, the mechanism for how the dNK cells play such important roles in successful pregnancy remains undefined. Here, we identified a subtype of dNK cells characterized as having a CD3(−)CD56(bright)CD25(+) phenotype. We found that CD56(bright)CD25(+) NK cells preferentially localize to the maternal/fetal interface during early human pregnancy. CD25(+) dNK cells account for approximately 75% of CD25-expressing decidual immune cells (DICs). However, less than 5% of CD25-positive peripheral blood mononuclear cells are CD25(+) NK cells. Furthermore, CD25(+) and CD25(−) dNK cells exhibit distinct phenotypes: CD25(+) dNK cells display a more activated phenotype and greater cytokine-secreting capacity. Interestingly, coculture of peripheral NK (pNK) cells with primary trophoblasts upregulates the percentage of CD25-expressing pNK cells, resulting in increased expression of activation markers and cytokine production by pNK cells. In addition, we demonstrated that the CXCL12/CXCR4 axis is crucial for the recruitment of CD25(+) dNK cells and contributes to the accumulation of CD3(−)CD56(bright)CD25(+) dNK cells at the maternal/fetal interface. Thus, our data reveal that the crosstalk between trophoblasts and pNK cells leads to the accumulation of CD3(−)CD56(bright)CD25(+) dNK cells, which exert a regulating effect at the maternal/fetal interface.